Hydroelectric Power Station - Michael Becker; Franz G. Schröck; Bernhard Kast (Oz, 2012)
On the left bank of the Iller River, a new, highly efficient hydroelectric power station has been built to replace an older power station from the 1950s. The power station supports approximately three thousand households with 10.5 million kilowatt-hours of environmentally friendly power per year.